Pediatric conjunctival melanoma: A comprehensive case report and literature review - Cantú-Soriano, Gonzalo N.; Sánchez, N. G.; Suárez-Reynoso, L.; Padilla Rodríguez, Álvaro Lezid (Elsevier, 2024)
Purpose: This case report aims to present a rare instance of conjunctival melanoma in a 5-year-old patient and contribute to the limited body of knowledge on pediatric conjunctival melanoma. The purpose is to understand the characteristics, diagnosis, and management of this uncommon malignancy in young individuals. Observations: The case describes a 5-year-old female with a progressively growing pigmented conjunctival lesion. The lesion was observed to be located on the temporal conjunctiva of the right eye and displayed distinctive features, including feeder vessels. Imaging revealed specific dimensions of the lesion and ruled out deeper invasions. Histopathological examination revealed architectural and cytologic atypia, positive immunohistochemical staining for HMB-45, and a Ki67 proliferation index of 20 %, confirming the diagnosis of conjunctival melanoma. ©American Journal of Ophthalmology Case Reports.
Keywords: Pediatric; Conjunctival; Melanoma